Comparative Study Infused Mechanism Among Absorbance Materials to Improve Plant Growth - Wan Malik, Wan Mohammad Hakim; Harun, Zawati; Harith, Fazlannuddin Hanur; Azhar, Faiz Hafeez; Ismail, Anuar (Emerging Advances in Integrated Technology, 2025)
Agriculture is the practice of cultivating land, growing crops, and raising livestock for human consumption. The purpose of this experiment is to assess how successful zeolite, charcoal, and kaolin are as slow-release fertilizers by investigating the adsorption performance of zeolite as a nutrient-uptake agent using various samples. This paper discussed the three absorbents when infused with the fertilizer towards plant growth potentially for soil quality, conservation of water, and nutrient consumption. Since the infused absorbent shows the best quality in the retention of water and nutrients, it enables it to collect hazardous substances quickly and efficiently from environmental pollution. The mixture of the sample contains 80 grams of soil and 5 grams of infused zeolite, charcoal, and kaolin for planting green beans. Absorption and fertilizer testing were performed to see the physical properties of infused absorbent samples. In conclusion, the ability of zeolite and kaolin to retain nutrients was performed the best while charcoal slightly displayed growth of the plants as shown by the result of the height, length of leaf, pH level, and humidity of the soil.